Performance assessment of a 10 kW pressurized solid oxide fuel cell integrated with glycerol supercritical water reforming - Yaneeporn Patcharavorachot; Narissara Chatrattanawet; Dang Saebea; Amornchai Arpornwichanop (International Journal of Energy Research, 2022)
Summary In this work, the integrated system of pressurized solid oxide fuel cell (SOFC) and supercritical water reforming of glycerol was proposed. The syngas from the reforming process has high temperature and pressure and thus, it can be used as fuel for the SOFC. The performance of an integrated system was determined through the Aspen Plus simulator in which the electrochemical equations were also included. The developed model was employed to examine the performance of the integrated system with respect to the wider ranges of operation of the reformer and SOFC. In this work, the desired power output of an SOFC stack is set as 10 kW and thus, the area of an SOFC is determined. A smaller area is required as it normally leads to a lower fabrication cost for the SOFC. The simulation results revealed that the smallest SOFC area can be provided when the reformer is operated at 800°C and 240 atm with a ratio of supercritical water to glycerol as 50 whereas the SOFC operation is at 900°C and 4 atm with the current density as 7000 A/m 2 . Under these operating conditions, the integrated system can provide the cell voltage, required area, fuel utilization, and SOFC efficiency as 1 V, 1.42 m 2 , 75% and 61%, respectively. From the exergy analysis, it was found that the compressor, heater, and turbine are the highest exergy destruction units whereas the reformer has the lowest exergy destruction, followed by the SOFC stack.
Keywords: Subcritical and Supercritical Water Processes; Catalysts for Methane Reforming; Electrocatalysts for Energy Conversion